Resiliensi Pasien GGK yang Menjalani Hemodialisa - I Nengah Sumirta; I Wayan Candra (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2016)
The purpose of this study is to find resiliensi in patients CFR who underwent hemodialisa at RSUD Wangaya. The kind of research this is research descriptive, uses the approach subject cross sectional, data collection using a technique purposive sampling. Data collection instrument that is used is cd-risc of Conor-Devidson. The total sample 51 patients who underwent ggk hemodialisa at RSUD Wangaya. The sample of the 51 patients ggk who underwent hemodialisa. The research results show that of 51 respondents there were 4 respondents (7.8%) have resiliensi high, 39 respondents (76,5%) have resiliensi being, and 8 respondents (15.7%) have resiliensi low. Based on gender highest number of the level of rsiliensi being in males as many as 30 people (58,8% ), the level of age dominated by the imago of madya thirty-one people (60.8 %), the level of education highest number of the secondary level by 17 people (33.3%), greatest percentage in work who works 29 people (56,9 %), based long undergo hemodialise dominated a period of time gt; 24 months as many as 22 people (43,2%) and according to the frequency of hemodialise dominated by tingat resiliensi being at the frequency of twice a week. Expected the result of this research can be used to develop the care of nursing especially on the psikososial patients ggk undergo hemodialisa.